Discourse analysis as an instrument to reveal the pivotal role of the media in local acceptance or rejection of a wildlife management project.: A case study from the Bavarian Forest National Park - Ludwig, Melanie; Grüninger, Frederike; Rothfuss, Eberhard; Heurich, Marco (ERDKUNDE, 2012)
Protected areas rate among the most popular nature conservation measures according to general public opinion in Germany. However, people living close to these sites do not always share this positive view. In fact, the implementation of such measures often leads to conflicts between the local resident population and management staff, which in many cases emanate from the failure to actively involve locals in the decision processes. Communication and participation are now acknowledged as crucial for the acceptance of nature conservation measures and are applied more and more in practice, but these factors do not guarantee the successful cooperation between the protected areas’ administration units and their inhabitants. Past experiences and events may have planted mistrust and antipathies now thoroughly embedded in the collective memory, and thus hinder successful results in future decision-making processes. By means of discourse analysis, we examined a bottom-up process initiated in the Bavarian Forest National Park (southern Germany) concerning the future management of its red deer population. This exemplary study reveals the pivotal role the media plays in presenting the public discourse on nature conservation issues in general, and which discursive elements may have led to the final failure of the project in the case study presented.